1987
DOI: 10.1159/000248779
|View full text |Cite
|
Sign up to set email alerts
|

Light- and Electron-Microscopic Findings in Lichen sclerosus of the Vulva during Etretinate Treatment

Abstract: Fifteen women with lichen sclerosus (LS) of the vulva were treated for 3 months with 0.6 mg/kg of etretinate. The clinical response was good in 11/15 of the patients and, in agreement with this, light microscopy showed decreasing atrophy and hyperkeratosis together with subsiding inflammatory changes. However, orcein staining demonstrated that even after etretinate treatment, elastic fibers were still absent in the upper dermis with only few fibers being detectable in some specimens. Conventional electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Mihara et al 5 found that remaining elaunin fibers in early LS were normal but were pushed downwards, probably from deposition of acid mucopolysaccharides. Rompannen et al 23 suggested that the changes in elastic fibers were similar to those obtained experimentally with elastase, and raised the possibility that elastic fiber damage in LSA might be a function of inflammatory cell‐mediated enzymatic digestion. Higher elastase‐like activity has been showed in vulvar LS in comparison with normal vulvar skin 22 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Mihara et al 5 found that remaining elaunin fibers in early LS were normal but were pushed downwards, probably from deposition of acid mucopolysaccharides. Rompannen et al 23 suggested that the changes in elastic fibers were similar to those obtained experimentally with elastase, and raised the possibility that elastic fiber damage in LSA might be a function of inflammatory cell‐mediated enzymatic digestion. Higher elastase‐like activity has been showed in vulvar LS in comparison with normal vulvar skin 22 .…”
Section: Discussionmentioning
confidence: 65%
“…A study of early histopathological changes in LS revealed loss of elastic fibers in 100% of cases, suggesting that it is an early finding 7 . Most electron microscopic studies on LS confirm the decrease in elastic fibers within the homogenized zone 5,20–23 . However, the underlying cause or mechanism behind the decrease and loss of elastic fibers is not known.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand the disappearance of elastic fibers in the upper dermis has been observed in LSA (11)(12)(13)(14), but this fact has not been emphasized or been disseminated well. Romppanen et al (15) point up this lack of emphasis in their light microscopic and electron microscopic studies of LSA. Their immunoelectron microscopic findings in LSA show that there was only occasional positive reaction for elastic material in the superficial dermis.…”
Section: Commentmentioning
confidence: 99%
“…Electron microscopy demonstrates altered collagen fibrils and fragmentation of elastin fibres. 2 We have demonstrated immunohistochemically that there are significant alterations around the upper dermis, basement membrane zone and epidermis which include infiltration of CD4 and CD8 cells at these sites, 3 expression of HLA‐DR around the keratinocytes, 3 significant alteration of the basement membrane proteins, 4 increased expression of tenascin and reduced expression of fibronectin. 5 …”
Section: Introductionmentioning
confidence: 93%